Influencia de las redes sociales en el desarrollo de tareas académica en estudiantes de secundaria de la Institución Educativa I.P.S. N° 601582 Agustín Rivas Vásquez, Tamshiyacu 2024 - Cardenas Millar, Anita Milagros (2025)
The objective of this thesis was to determine the relationship of social networks in the development of academic tasks in high school students of the Initial, Primary and Secondary Educational Institution N° 601582 Agustín Rivas Vásquez - Tamshiyacu, 2024, in the methodology was applied the non-experimental type with a descriptive-correlational design, where we worked with a population of 55 students of 5th year of high school, The sample was of a census type, that is, 100% of the population where the survey technique was used to identify the characteristics of the social networks they use by means of a questionnaire, as well as indirect observation by applying an evaluation card, to recognize the development of academic tasks. It was found that for the use of social networks 34.5% of the students indicated that they use social networks for academic activities and when evaluating their academic tasks, 32.7% obtained good grades; these data were expressed in cross tables and the hypothesis test was applied with Spearman's Rho statistic, where a p-value of less than 0.05 was obtained. 7% obtained good grades; these data were expressed through cross tables and the hypothesis test was applied with Spearman's Rho statistic where a p-value of less than 0.05 was obtained; which concludes that there is a relationship between social networks in the development of academic tasks in high school students of the Initial, Primary and Secondary Educational Institution N° 601582 Agustín Rivas Vásquez - Tamshiyacu in the year 2024, proving the objectives and hypotheses raised.